PENGARUH MEDIA PEMBELAJARAN VIDEO TERHADAP PUKULAN FOREHAND DAN BACKHAND PADA PERMAINAN TENIS MEJA - Ronald Dwi Ardian Fufu; Al Ihsan Tajuddin; Maria Barek Ladjar (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
ABSTRACTTargeted learning can make a significant contribution to achieving learning goals. One of the obstacles experienced by the fourth semester students of Class B of the FKIP Undana Penjaskesrek Study Program is the lack of attention and motivation to learn which often has an impact on forehand and backhand. Video learning media is audio visual media that displays motion, which can present live images, not only sounds that we can hear but visually also from the video in the teaching and learning process, the material presented will be more interesting, and not boring and foster motivation to learn. The purpose of this study was to determine the effect of video learning media on forehand in table tennis and to determine the effect of video learning media on backhand shots on table tennis. This type of research that researchers use is quasi-experimental with a quantitative descriptive approach. The research design used was One Group Pretest-Posttest Design. Based on the results of statistical tests using SPPS with Paired Sample T-Test, the Sig (2-tailed) value of the Forehand shot is 0,000 and Backhand is 0,000, all of which are <0.025 then Ho is rejected so H1 is accepted. In other words, there is a significant influence of video learning media on forehand and backhand in table tennis.Keyword: Learning Video, Forehand, Backhand, Table Tennis